AGRIBISNIS PERKEBUNAN MEMASUKI AWAL ABAD 21: BEBERAPA AGENDA PENTING - SUSILA, WAYAN R.; DRADJAT, BAMBANG (SOCA: Jurnal Sosial Ekonomi Pertanian; Vol. 1, No. 1 Februari 2001, 2012)
Estate-crop agribusiness has played and is still expected to play important roles in Indonesian economy. Besides its consistent contribution on economic growth and foreign exchange earning, it provides employment for more than 13 million people. In the beginning of 21st century, the estate-crop agribusiness will face various new important agenda and strategic business environment changes related to this subsector, namely, production cost, commodity prices, market competition, trade liberalization, production policies, trade policies, regional autonomy, environmental issues, and plantation plundering. Some of them will depress the development of the subsector in the beginning of 21st century, while the others will provide better opportunities for the development of the subsector or their net impacts are still vague. To optimize the roles of the estate-crop subsector agribusiness, various important agenda and strategic business environment changes related to the subsector should be managed in a such way that the negative impacts of the changes can be minimized while the positive and vague impacts can be converted to be a growth engine of the subsector in entering the beginning of 21th century.
Keywords: Estate-Crop Agribusiness, Indonesian Economy, Economic Growth, Foreign Exchange Earning.